Respuesta :
Answer:
Your answer is 2x³ + 7x²y + y²- x²
Step-by-step explanation:
(a) ( 2x³ + 4x²y + 5xy² - 3y² ) - ( x² - 3x²y +5xy² - 2y² )
= 2x³ + 4x²y + 5xy² - 3y² - x² + 3x²y - 5xy² + 2y²
= 2x³ + 4x²y + 3x²y + 5xy² - 5xy² + 3y² + 2y² - x²
= 2x³ + 7x²y + y²- x² ans.
Hope its helpful!
Please mark me as brainlist.
Step-by-step explanation:
(a) ( 2x³ + 4x²y + 5xy² - 3y² ) - ( x² - 3x²y +5xy² - 2y² )
= 2x³ + 4x²y + 5xy² - 3y² - x² + 3x²y - 5xy² + 2y²
= 2x³ + 4x²y + 3x²y + 5xy² - 5xy² + 3y² + 2y² - x²
= 2x³ + 7x²y + y²- x² ans.